2015
DOI: 10.1186/s12866-015-0441-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Acinetobacter baumannii in different hospitals in Tripoli, Lebanon using bla OXA-51-like sequence based typing

Abstract: BackgroundA. baumannii has emerged as an important nosocomial pathogen with an outstanding ability to acquire multidrug resistant mechanisms. In this study, we investigate the molecular epidemiology and carbapenem resistance mechanisms of A. baumannii in Tripoli, Northern Lebanon.MethodsOne hundred sixteen non-duplicate isolates isolated between 2011 and 2013 in different hospitals in Tripoli, Lebanon from Lebanese patients and wounded Syrian patients during Syrian war were studied. Antibiotic susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 49 publications
9
48
0
Order By: Relevance
“…In accordance with other studies performed in Lebanon, IC II was by far the most prevalent clone among the A. baumannii isolates (Rafei et al, 2014) and OXA-23-like is the most disseminated (Rafei et al, 2015). These findings are also similar to those reported from other Mediterranean countries (Di Popolo et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with other studies performed in Lebanon, IC II was by far the most prevalent clone among the A. baumannii isolates (Rafei et al, 2014) and OXA-23-like is the most disseminated (Rafei et al, 2015). These findings are also similar to those reported from other Mediterranean countries (Di Popolo et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…In 2012, 88% of 724 A. baumannii isolates recovered from various Lebanese hospitals were found to be resistant to imipenem (Hammoudi et al, 2015a). Although OXA-24-like (Hammoudi et al, 2015b) and OXA-58-like (Zarrilli et al, 2008) have been detected in this country, OXA-23-like seems to be the most prevalent among CRAB isolates (Rafei et al, 2015). …”
Section: Introductionmentioning
confidence: 97%
“…2226C was isolated in Turkey in 2009 while ABC002 was collected in Egypt in 2011 (https ://pubml st.org/). ST158 isolates were also reported in Lebanon between 2011 and 2013 [42]. The recognition of Ab-Pak-cluster-7 in Pakistan has then expanded the geographic distribution of ST158 beyond the Middle East [43][44][45][46].…”
Section: Ab-pak-cluster-7 a New Member Of Clone St158mentioning
confidence: 99%
“…ST1 and ST1106 shared identical alleles in 5/7 of the loci. Ab-Pak-cluster-7 was assigned to ST158 (41,42,13,1,5,4,14). The individual isolates Ab-Pak-Pesh-04 and Ab-Pak-Pesh-22 belonged to ST25 (3, 3, 2, 4, 7, 2, 4) and ST23 (1,3,10,1,4,4,4), respectively.…”
mentioning
confidence: 99%
“…In Lebanon, numerous recent studies reported an increasing high rates of resistant bacteria isolates from clinical and commensal sources to most antimicrobials [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, few data about the bacterial ear pathogens in Lebanon is available.…”
Section: Introductionmentioning
confidence: 99%